Pengembangan Sistem Informasi Keluarga Sejahtera sebagai Tools Pendataan Posdaya - Irwanti, Nur Endah; Djuniadi, Djuniadi; Supraptono, Eko (Edu Komputika Journal, 2016)
The aim of this research is to build a prosperous family information system, and to test the validity and feasibility. The method used is the Research and Development, with three stages. The preliminary study stage aims to uncover the facts which related to data collection. The development phase includes the products making (analysis, design, and implementation or coding), and also product validation. The evaluation phase to test the limited scale of the KKN students. Instrument testing using ISO-9126 standard. The results showed that the information system of prosperous family has been successfully developed, client (android) and server (web). Validation of the material has a percentage of 94.167%, the validation system (server) amounted to 91.67%, the validation application (client) amounted to 92.22%, thus declared valid by the criteria very well, and the user test of 87.44%, to be feasible with the criteria very well too. The suggestions put forward is to test the vast scale of the field and the need for the development of information systems featured on both server and client.